Tatapan Bijak: Mengembangkan Pemahaman terhadap Prinsip Kasih dalam Menyikapi “Toxic Relationship” di Kalangan Kaum Muda - Fany Sondakh (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2022)
This research explores the role of the principle of love in addressing toxic relationships and friendships among young adults. Using a mixed-methods approach combining textual analysis and interviews, we investigated vital concepts related to the principle of love, toxic relationships, and strategies for addressing these issues. Through data analysis, we found that applying the principle of love can help young adults repair or end harmful relationships and friendships wisely and empathetically. These findings have practical implications for developing youth service programs and interventions to support young people's mental and emotional well-being in interpersonal relationships.